Caliber-Persistent Artery - Sabrina Araújo Pinho Costa; Marcelo Martinson Ruiz; Shajadi Pardo Kaba; Giovanna Piacenza Florezi; Celso Augusto Lemos Júnior; Andréa Lusvarghi Witzel (Case Reports in Dentistry, 2015)
Caliber-persistent artery (CPLA) of the lip is a common vascular anomaly in which a main arterial branch extends to the surface of the mucous tissue with no reduction in its diameter. It usually manifests as pulsatile papule, is easily misdiagnosed, and is observed more frequently among older people, suggesting that its development may involve a degenerative process associated with aging; CPLA is also characterized by the loss of tone of the adjacent supporting connective tissue. Although the diagnosis is clinical, high-resolution Doppler ultrasound is a useful noninvasive tool for evaluating the lesion. This report describes the case of a 58-year-old male patient who complained of a lesion of the lower lip with bleeding and recurrent ulceration. The patient was successfully treated in our hospital after a diagnosis of CPLA and is currently undergoing a clinical outpatient follow-up with no complaints.